ENLARGING THE SURFACE AREA OF MONOLAYER GRAPHENE SYNTHESIZED BY MECHANICAL EXFOLIATION - G. Sh. Shmavonyan; G. G. Sevoyan; V. M. Aroutiounian
A method of enlarging the surface area of monolayer graphene produced by mechanical exfoliation of graphite and increasing the possibility of obtaining monolayer graphene is suggested. The enlargement of the surface area of monolayer graphene is due to additionally cleaving few layer grapheme adjacent to the monolayer. Raman spectroscopy and atomic force microscopy (AFM) are used to characterize as-prepared and enlarged areas of monolayer graphene and distinguish it from few layer graphene and graphite.
Keywords: Physics; Materials science